2021
DOI: 10.7554/elife.62174
|View full text |Cite
|
Sign up to set email alerts
|

Iron derived from autophagy-mediated ferritin degradation induces cardiomyocyte death and heart failure in mice

Abstract: Heart failure is a major public health problem, and abnormal iron metabolism is common in patients with heart failure. Although iron is necessary for metabolic homeostasis, it induces a programmed necrosis. Iron release from ferritin storage is through nuclear receptor coactivator 4 (NCOA4)-mediated autophagic degradation, known as ferritinophagy. However, the role of ferritinophagy in the stressed heart remains unclear. Deletion of Ncoa4 in mouse hearts reduced left ventricular chamber size and improved cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 39 publications
(43 reference statements)
2
71
0
Order By: Relevance
“…of autophagy that contributes to the initiation of ferroptosis through the degradation of ferritin by lysosomes (Qin et al, 2021;Zhou et al, 2020). Nuclear receptor coactivator 4 (NCOA4), a selective cargo receptor, promotes ferritin degradation during ferritinophagy (Goodall and Thorburn, 2014;Ito et al, 2021;Nai et al, 2021). The accumulation of ferrous iron triggers ROS generation through the Fenton reaction, and ferritinophagy modulates ferroptosis by increasing the levels of lipid peroxidation (Ajoolabady et al, 2021).…”
Section: Accessmentioning
confidence: 99%
“…of autophagy that contributes to the initiation of ferroptosis through the degradation of ferritin by lysosomes (Qin et al, 2021;Zhou et al, 2020). Nuclear receptor coactivator 4 (NCOA4), a selective cargo receptor, promotes ferritin degradation during ferritinophagy (Goodall and Thorburn, 2014;Ito et al, 2021;Nai et al, 2021). The accumulation of ferrous iron triggers ROS generation through the Fenton reaction, and ferritinophagy modulates ferroptosis by increasing the levels of lipid peroxidation (Ajoolabady et al, 2021).…”
Section: Accessmentioning
confidence: 99%
“…Because that NCOA4 is necessary for the implementation of ferritinophagy, ferritinophagy can be hindered by deleting or inhibiting NCOA4 (Hou et al, 2016;Ito et al, 2021). For more persuasiveness that NCOA4-dependent ferritinophagy is the mechanism of FA-induced neurotoxicity, we purposefully silenced NCOA4 in HT22 cells before FA treatment through shRNA interference technology to investigate whether inhibiting NCOA4-dependent ferritinophagy reverses toxic damage resulting from FA.…”
Section: Discussionmentioning
confidence: 99%
“…In iron therapies intended to improve AMI, the dose and time point of administration must be taken into the consideration, as higher iron concentrations generate oxidative stress and activate programmed apoptosis. 26 , 27 Additionally, lower concentrations of iron promote cell survival through increased inducible nitric oxide synthase activity and increased nitric oxide production. 28 , 29 In this study, we applied a dose of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that the time point of iron treatment during AMI appears harmful in the acute phase of AMI, in particular during reperfusion, which is caused by mitochondrial iron accumulation and leads to impaired cardiac contractility due to increased ROS within the cardiomyocytes. 33 Besides, these toxic effects of early iron application during or prior to reperfusion were prevented by the administration of iron chelator DFO 15 min prior to and 15 min throughout of coronary occlusion of reperfusion, which showed a cardioprotective effect through improved myocardial high‐energy phosphate metabolism and LV contractility after a period of global ischaemia. 13 These data support that iron catalysis is involved in the production of oxygen‐derived free radicals during I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation